The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 25th International Conference on Telecommunications (ICT) 2018
DOI: 10.1109/ict.2018.8464885
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Evaluation of Energy Budget Estimation Algorithms for Autonomous Long Range IoT Nodes

Abstract: In order to enable IoT nodes to efficiently use their energy harvesting capabilities, algorithms are used to determine a reasonable energy budget and allocate it to the node tasks, enabling energy neutral operation. However, most of these algorithms have been implemented and evaluated in simulation frameworks. In this paper, we evaluate the implementation of these algorithms to manage the energy of real-world LoRaWAN IoT nodes. We measure and compare the performance of the different energy budget estimation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Moreover, as the delay between two EBE executions can be long, it is necessary to use a model-free EBE algorithm that can converge towards an optimized duty cycle in a few executions. However, previous work [ 41 ] has shown that EBE algorithms have low performance differences when they are properly optimized, which enables the use of simple algorithms to compute . For this study, LQ-tracker [ 25 ] is used as the EBE algorithm, since it provides good performance without requiring its parameters to be tuned.…”
Section: Multi-source Multi-task Node Architecturementioning
confidence: 99%
“…Moreover, as the delay between two EBE executions can be long, it is necessary to use a model-free EBE algorithm that can converge towards an optimized duty cycle in a few executions. However, previous work [ 41 ] has shown that EBE algorithms have low performance differences when they are properly optimized, which enables the use of simple algorithms to compute . For this study, LQ-tracker [ 25 ] is used as the EBE algorithm, since it provides good performance without requiring its parameters to be tuned.…”
Section: Multi-source Multi-task Node Architecturementioning
confidence: 99%
“…To sum up, there is currently no commercial LoRa-based platform powered by energy harvesting but only few research works that mainly focus on the validation of the SW (energy manager) part [18,20] and do not address the dimensioning of the hardware elements [7].…”
Section: Related Work On Energy Harvesting For Long-range Platformsmentioning
confidence: 99%